Household Supply Access and Community Impact During Flood - Mat Rapi, Siti Nur Farhanna; Hashim, Hani Kalsom (Semarak International Journal of Transportation and Logistics, 2026)
This study explores the lived experiences of households in Kampung Paya Besar, Hulu Terengganu, during flood disasters, with a focus on access to basic supplies, challenges faced, coping mechanisms, and the role of community networks. Using a qualitative design, six semi-structure interviews were conducted with residents responsible for managing household supplies, and the data were analysed using a thematic analysis framework. The findings revealed that households obtained supplies through various strategies such as pre-flood shopping, wading through shallow waters, and using boats, although access often remained dependent on external aid. Challenges in accessing essential items were largely due to severe infrastructure damage, transportation breakdowns, and stock shortages, with the difficulties being more pronounced for vulnerable groups. To cope with shortages, households resorted to rationing food, sharing with neighbours, and stockpiling before the flood season, although these measures were often temporary. Community networks and institutions, including local leaders, mosques, NGOs, and government agencies, played important roles in delivering aid, however, mismatches between the aid provided and actual household needs persisted. Overall, the study highlights that while community resilience and informal networks are essential, systemic issues such as infrastructure limitations, uncoordinated aid distribution, and the absence of needs-based planning continue to hinder effective disaster response. Recommendations include establishing localised aid storage, providing customised relief packages, and enhancing community-based logistics training to strengthen preparedness and response in flood-prone rural areas.